The Benson Relaxation Technique The Effect Of The Benson Relaxation Technique On Sugar Blood Levels Blood In Type 2 Diabetes Mellitus Patients At Tangerang District Hospital: The Effect Of The Benson Relaxation Technique On Sugar Blood Levels Blood In Type 2 Diabetes Mellitus Patients At Tangerang District Hospital - siti rohayani -; Kusniawati Kusniawati (Journal of Smart Nursing and Health Science, 2024)
Introduction: Diabetes Mellitus (DM) is a group of metabolic disorders characterized by an increase in blood glucose levels (hyperglycemia) caused by abnormalities in insulin secretion, insulin action, or both. A nonpharmacological therapy that can be used as a companion to pharmacological therapy is Benson's relaxation technique. Benson's relaxation technique produces a relaxed state so that it can suppress hormones that cause blood sugar levels to rise such as epinephrine, cortisol, glucagon, ACTH corticosteroids, and thyroid. Objective: This study was to determine the effect of Benson's relaxation technique on blood sugar levels in Type 2 Diabetes Mellitus patients. Method: The research design used experimental queasy, with one group pretest-posttest design. The sampling technique in this study used purposive sampling with a total sample of 28 respondents conducted from April 13 to April 29, 2023, in the inpatient room of the Tangerang Regency Regional General Hospital. Then the data of this study was analyzed using paired t-tests. Results: Average GDS value before intervention 306.25 mg/dl and after intervention 276.57 mg/dl with p-value = 0.000 (<0.05). Conclusion: In this study, there was an effect of Benson's relaxation technique on reducing blood sugar levels in Diabetes Mellitus patients.